Cu:NiO as a hole-selective back contact to improve the photoelectrochemical performance of CuBi2O4 thin film photocathodes. Issue 15 (27th March 2019) - Song, Angang; Plate, Paul; Chemseddine, Abdelkrim; Wang, Fuxian; Abdi, Fatwa F.; Wollgarten, Markus; van de Krol, Roel; Berglund, Sean P.
Abstract : Cu doped NiO (Cu:NiO) back contact layers are inserted between FTO substrates and CuBi2 O4 thin films to improve the performance of CuBi2 O4 photocathodes. Abstract : P-type CuBi2 O4 has recently been reported as a promising photocathode material for photoelectrochemical water reduction due to its optimal optical band gap and positive photocurrent onset potential. However, despite these favourable attributes, CuBi2 O4 photocathodes have shown limitations in charge carrier transport within CuBi2 O4 and across the interface with n-type fluorine doped tin oxide (FTO). To overcome the later limitation, a very thin and transparent p-type Cu doped NiO (Cu:NiO) back contact layer is inserted between the FTO substrate and CuBi2 O4 . The Cu:NiO layer is prepared by electron beam evaporation of Ni and Cu followed by post annealing in air. CuBi2 O4 photocathodes with a 7 nm thick Cu:NiO back contact layer produce photocurrent densities up to 2.83 mA cm −2 at 0.6 V versus RHE under back illumination with H2 O2 as an electron scavenger, which is 25% higher than photocathodes without the back contact layer. This is also the highest reported photocurrent density for CuBi2 O4 to date. The observed improvement in photocurrent density with the Cu:NiO back contact layer is attributed to hole selective transport across the CuBi2 O4 –Cu:NiO interface with a decrease in barrier height compared to the CuBi2 O4 –FTO interface.